(untitled) (Global Conference on Medical and Health Sciences, 2026)
Oxidative stress has emerged as a fundamental pathological mechanism contributing to neuronal damage and the progression of neurodegenerative diseases. It is characterized by an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defense system, leading to cellular dysfunction and structural damage. Neurons are particularly vulnerable to oxidative stress due to their high metabolic demand, lipid-rich composition, and limited regenerative capacity.